2022
DOI: 10.1016/j.jds.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of five irrigation techniques in removing calcium hydroxide from simulated S-shaped root canals

Abstract: Background/purpose Calcium hydroxide [Ca(OH) 2 ], a wildly used intracanal medicament, should be completely removed from the root canal before obturation to avoid negative effects on the treatment. This study evaluated the effectiveness of conventional needle irrigation (CNI), passive ultrasonic activation (PUI), photon-induced photoacoustic streaming (PIPS), XP-endo Finisher (XP) and EDDY for the removal of Ca(OH) 2 from S-shaped root canal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
3
17
0
1
Order By: Relevance
“…The efficiency of removal from the coronal and middle thirds could be attributed to the larger diameter in these areas, exposing dentin to a higher volume of irrigants and making Ca(OH)2 removal easier. This was in accordance with the findings of Shi et al (26). On the other hand, EDDY sonic activation was reported by Donnermeyer et al (6) to achieve the best results in the apical third.…”
Section: Discussionsupporting
confidence: 93%
“…The efficiency of removal from the coronal and middle thirds could be attributed to the larger diameter in these areas, exposing dentin to a higher volume of irrigants and making Ca(OH)2 removal easier. This was in accordance with the findings of Shi et al (26). On the other hand, EDDY sonic activation was reported by Donnermeyer et al (6) to achieve the best results in the apical third.…”
Section: Discussionsupporting
confidence: 93%
“…As consistent with previous research, results from this study also indicated that none of the proposed techniques removed 100% of CH from artificial IRR cavities. [ 1 2 7 8 9 14 19 20 21 ] Although to facilitate scoring without bias, cavities were made by no. 2 round diamond bur to standardize dimensions, location of resorption cavities, and quantity of medicament used.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this study [ Figure 3 ], PUI and XP-endo were able to remove complete CH in 55% of specimens, where IRR cavities were free of any debris which was significantly higher than EA (25%) and EI (5%). Several authors explained that during PUI, acoustic microstreaming and cavitation can cause a streaming pattern within the root canal from apical to coronal, which removes CH more effectively[ 1 2 6 7 8 9 11 14 19 20 21 ] as compared with sonic (EA) and syringe delivery (EI) system. Therefore, similar to previous studies,[ 1 2 6 7 8 9 ] this study also concluded that PUI possesses a great aptitude for clearing remote areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, most ultrasonic devices which are used for passive ultrasonic irrigation (PUI) operate at 25–30 kHz [ 21 ]. As the gold standard of irrigant activation [ 22 ], PUI transmits the acoustic energy from an oscillating file or smooth wire to an irrigation solution in the root canals [ 23 ]. Compared with the traditional methods of root canal irrigation, the classic PUI devices have effectively improved root canal disinfection through the generation of cavitation and acoustic transmission [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%